The Role of Accountability in the Belgian Education System: From Control Regulation to Autonomous Regulation - Renard, Fabienne; Derobertmasure, Antoine; Demeuse, Marc (International Journal of Education Policy and Leadership, 2023)
Since 2017, new modes of regulation have been implemented in French-speaking Belgium and have resulted in responsibilization and accountability policies. This article aims to define the characteristics of control regulation, which corresponds to explicit and official rules implemented by the central government. Based on a textual analysis (NVivo® software) of legal texts published between 2017 and 2019, it aims to understand this regulation. This article consists, firstly, of an analysis of the way in which these texts define concepts reflecting the reform of governance in French- speaking Belgium (accountability, autonomy, etc.). Secondly, the “consistency” between this analysis and the literature is examined. This analysis is enriched by a qualitative analysis of interviews conducted with stakeholders in the system (N = 5) regarding the way they mobilize these concepts. The aim is to approach autonomous regulation, corresponding to the rules produced within the organization by the individuals who make it up and their interpretation, so that it corresponds to their “reality in the field.” Based on these levels of analysis, this article intends to identify the extent to which these stakeholders take up the meaning of these concepts from the corpus and/or the literature in their discourse, but also how they alter, deviate from, or interpret it.